Executive functions in sarcoidosis: a neurocognitive assessment study - Bilgin Topçuoğlu, Özgür; Kavas, M.; Alibaş, Hande; Çetintaş Afşar, Gülgün; Arınç, Sibel; Midi, İpek and Tuncer Elmacı, Neşe (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
Not available